Quality Attributes Of Bread Using Mango (Mangifera Indica) Peel Flour - Ch'ng, Weng Kee (2011)
The objective of this research was to evaluate the physical, nutritional and sensory attributes of composite flour breads. Substitutions of white bread flour with mango peel flour (MPF) were carried out at 5 %, 10 % and 15 % levels. Physico-chemical and functional properties of both fresh mango peel (FMP) and mango peel flour (MPF) were also determined. Increasing levels of substitution with MPF 5-15 % to white bread flour significantly increased (p<0.05) the moisture and crude fibre content and decreased the protein, fat and carbohydrate. The FMP and MPF substituted bread were rich in potassium.